Let All Voices Be Heard!: Exploring International Students’ Communication Challenges in the Internationalized Classroom - Yu, Xi; Peters, Bethany (Journal of Interdisciplinary Studies in Education, 2019)
In many cases, faculty and staff are unaware of the unique challenges that international students experience in classrooms, and teaching priorities may not be aligned with the learning needs.  To address the gap in perspectives between students and faculty/staff, this focus group study involved international students, staff, faculty and instructors.  The purpose is to identify barriers that international students face in cross-cultural interaction, and develop strategies that faculty and staff can use to provide effective support.  The study reveals multi-layered challenges that cross-cultural transition and language barriers can create for international students, and roles of domestic students in cross-cultural interactions.  The resulting discussion highlights teaching and advising strategies that faculty/staff can employ to enhance the learning experience for international students.